RICE FIELD CONVERSION INTO PALM OIL PLANTATIONS IN TINOKKAH VILLAGE, SIPISPIS, SERDANG BEDAGAI REGENCY - Lily Fauzia; Dian Pebriyani; Yose Helen Br Damanik; Mozard Bahauddin Darus; Siti Khadijah Hidayati Nasution (CV. Radja Publika, 2026)
Rice remains the staple food of most Indonesian households, yet the sustainability of domestic rice production is increasingly threatened by the conversion of paddy fields into oil palm plantations. This study analyses the factors influencing the percentage of paddy field converted into oil palm plantations in Tinokkah Village, Sipispis Subdistrict, Serdang Bedagai Regency, North Sumatra. Using a census of 29 farmers who had converted part or all of their paddy fields between 2019 and 2025, primary data on sociodemographic, farming, and economic characteristics were collected and analysed using descriptive statistics and a Tobit regression model, with the percentage of converted land (0–100%) as the censored dependent variable. The results show that farmers converted a large share of their land, averaging 80.67%, with conversions concentrated after 2022. The Tobit estimation indicates that rice production cost before conversion has a negative and statistically significant effect on the percentage of converted land (p < 0.01), whereas rice farming income and farming experience are not significant. These findings reveal a trade-off between household economic rationality and local food sustainability, implying that maintaining paddy fields requires both regulatory control over land conversion and economic incentives that keep rice farming viable for smallholders.